Green Purchasing Adoption Of Construction Companies In Malaysia - Hadi, Nurul Huda Abdul (2025)
Green purchasing is when goods and services are purchased to decrease environmental impact and achieve desired long-term goals. In the construction sector, green purchasing refers to purchase environmentally friendly items and services for construction activities. Green purchasing is gaining traction in malaysia as companies recognise their responsibility to promote sustainability, with increasing consumer awareness driving environmentally conscious consumption. This research aims to establish a green purchasing adoption framework for malaysian construction companies by determining factors influencing green purchasing (gp) adoption, examining these factors and their relationship with adoption, and investigating the moderating effect of organisational culture on this relationship. This study tested fourteen hypotheses within a model based on a literature review. An empirical assessment was conducted through a survey of 187 respondents in peninsular malaysia, analysed using ibm spss 27 and smartpls 4 software. Five of the examined hypotheses were accepted. Corporate factors, material suppliers, and expected business benefits significantly predicted green purchasing adoption, while government regulations, stakeholder pressure, top management support, and subcontractor relationships did not lead to its adoption. Partial evidence suggests that organisational culture moderates the effect of government-subcontractor relationships on organisational culture.